Usprawnianie muzyczne małych dzieci - metoda Edwina E. Gordona = Improving musical skills of small children - Edwin E. Gordon`s method - Kuligowska, Emilia (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article presents methods of working with the youngest children who, according to the music learning theory, are at the stage of initial audiation. It explains the importance of movement in Edwin E. Gordon`s theory. Method of conducting classes for children aged up to 18 months is discussed in details.
Keywords: teoria uczenia się muzyki Edwina Gordona; audiacja wstępna; zajęcia umuzykalniające; muzykoterapia; podstawa programowa; music learning theory; initial audiation; musical skills development classes; music therapy; core curriculum